Insiders’ Purchases, Abnormal Returns, and Market Efficiency : Evidence from the Helsinki Stock Exchange - Tulokas, Otto (My University, 2025)
This thesis examines the abnormal returns of insiders’ stock purchases in the Helsinki Stock Exchange during the period 10/2019–12/2024. The findings show that an insider's corporate role significantly influences return magnitude: board members and CEOs achieve the highest abnormal returns, while other groups yield substantially lower results. Statistically significant cumulative abnormal returns are observed within a 10-day window, but the 30-day returns are not statistically significant for any group. A negative relationship emerges between transaction value and abnormal returns, likely driven by the underperformance of large shareholders, who account for the largest trades in the sample.

Tämä tutkielma tutkii sisäpiiriläisten osakeostojen epänormaaleja tuottoja Helsingin pörssissä aikavälillä 10/2019–12/2024. Tulokset osoittavat, että sisäpiiriläisen asema yhtiön sisällä vaikuttaa merkittävästi epänormaalien tuottojen suuruuteen: Sisäpiiriläisistä hallitusten jäsenillä sekä toimitusjohtajilla havaitaan suurimmat epänormaalit tuotot, kun taas muiden sisäpiiriläisten tuotot jäävät huomattavasti alhaisemmiksi. Tilastollisesti merkitseviä kumulatiivisia epänormaaleja tuottoja havaitaan 10 päivän aikaikkunassa, mutta 30 päivän kumulatiiviset epänormaalit tuotot ovat tilastollisesti merkityksettömiä kaikilla sisäpiiriläisillä. Ostojen rahamääräisen suuruuden ja epänormaalien tuottojen välinen yhteys osoittautuu negatiiviseksi, mikä todennäköisesti liittyy suurten osakkeenomistajien heikkoon suoriutumiseen, sillä he toteuttivat aineiston suurimmat kaupat.
Keywords: Insider trading, abnormal returns, market efficiency, Helsinki Stock Exchange, event study, sisäpiirin kaupat, epänormaalit tuotot, markkinatehokkuus, Helsingin pörssi, tapahtumatutkimus